Primordial gravitational waves in the cosmic microwave background - Clarke, Thomas James (2021)
The study of gravitational waves is one of the most exciting areas of modern physics. As a relatively young observational field it promises a great deal of new and important information about the Universe in which we find ourselves. This thesis investigates the behaviour of gravitational waves in cosmology. As such, it starts with details of: the standard model of cosmology, LambdaCDM; relevant observational techniques; techniques for data analysis and the theoretical and observational details of cosmological gravitational waves.